The Role of Commitment, Competence, Internal Control system, Transparency and Accessibility in Predicting the Accountability of Village Fund Management - Dewi Indriasih; Wiwit Apit Sulistyowati (The Indonesian Accounting Review, 2022)
Village fund management is an important challenge for village officials that can pose crucial potential in the use of such funds. Therefore, this study aims to test the accountability of village fund management reviewed from the commitment of village apparatus, competence of village apparatus, internal control system, transparency, and accessibility. The survey method through questionnaire instrument was con-ducted in 19 villages, with a total sample of 76 village apparatus. Based on the results of multiple regression analysis, it shows that accessibility is the most important factor in realizing accountability of village fund management. In addition, internal control systems and transparency have a positive effect on the accountability of village fund management. While the commitment and competence of village apparatus has no effect on the accountability of village fund management. This study contributes to the literature of village fund management both theoretically and practically.